2009
DOI: 10.1177/1099800409344620
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Review of Cytokines in Maternal, Cord, and Newborn Blood: Part I—Associations With Preterm Birth

Abstract: Preterm birth (PTB; spontaneous delivery prior to 37 weeks gestation) affects one out of eight infants born in the United States and is the most common cause of neonatal morbidity and mortality. Although the pathogenesis of PTB is multifactorial, a growing body of literature supports the hypothesis that one cause of PTB is inflammation in pregnancy. Investigators have implicated mediators of inflammation, most notably proinflammatory cytokines, as being associated with and perhaps a playing a causal role in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
68
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(71 citation statements)
references
References 48 publications
(22 reference statements)
1
68
2
Order By: Relevance
“…Unlike other published studies, we did not find significantly increased levels of IL-6, IL-8 and TNF-α in women delivering preterm [47,48]. There is a vast controversy in the literature regarding cytokine profiles and PTB.…”
Section: Page 7 Ofcontrasting
confidence: 55%
“…Unlike other published studies, we did not find significantly increased levels of IL-6, IL-8 and TNF-α in women delivering preterm [47,48]. There is a vast controversy in the literature regarding cytokine profiles and PTB.…”
Section: Page 7 Ofcontrasting
confidence: 55%
“…High cortisol levels (Erickson et al, 2001;Field et al, 2004;Hobel, Dunkel-Schetter, Roesch, Castro, & Arora, 1999;Kramer et al, 2010;Sandman et al, 2006) and a state of low grade inflammation characterized by higher serum levels of IL-1β, IL-6, IL-8 and TNF-α (Hasegawa et al, 2003;Vogel et al, 2007) have been associated with increased risk for preterm birth. Indeed, a recent systematic review found that women with preterm birth have increased levels of pro-inflammatory cytokines during pregnancy, particularly IL-6, IL-1β and TNF-α compared with women with full term birth (Lyon et al, 2010). Such a pro-inflammatory environment, due to either increased production of pro-inflammatory cytokines or decreased production of anti-inflammatory cytokines, may be instrumental in the etiology of preterm birth (Mulherin .…”
Section: Introductionmentioning
confidence: 95%
“…In addition to an essential role in bone health, growing evidence shows that vitamin D is involved in the inflammatory response (Adams and Hewison, 2008). Although inflammation has been linked to poor birth outcomes (Lyon et al, 2010), little is known about the relationship between vitamin D and inflammation during pregnancy. In the nonpregnant state, vitamin D is important in the regulation of the immune system and inflammation.…”
Section: Introductionmentioning
confidence: 99%